66 Scenes from America ; New Scenes from America - Leth, Jorgen; Holmberg, Dan (Danish Film Institute, 2008)
66 Scenes from America (1981): The film is a personal subjective impression, acutely sensed and perceived. The approach has been to register whatever exercises a fascination and place it in a surprising context. In Jørgen Leth's own words: "A documentary about the USA today. It embraces major and minor impressions, events, things, people, thoughts and feelings. It is a collection of pictures of a country which in many ways is strange and incomprehensible to us, but in which we nevertheless recognize a reflection of our own culture, and to which our dreams - whether we want them to or not - must bear a relation." [www.docreview.pl]
Keywords: DVD-Video